2023
DOI: 10.1007/s43153-023-00421-z
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic approach for synthesis of ZnO/NiO nanocomposites as a highly efficient photocatalyst and evaluation of their biological properties

T. D. Puttaraju,
T. L. Soundarya,
G. Nagaraju
et al.

Abstract: Mixed metal oxide-based nanocomposites (NCs) had remained broadly used for photo catalysisfacilitated elimination of harmful substances from the aquatic ecosystem. Now a days searching for an improved photo catalyst looks plentiful metal oxide-based materials take began out of studies. In present works concerning the use of ZnO/NiO NCs as photocatalytic treatment of wastewater utilizing oxides of metals as photo catalysts has merged a subject of major concern. The way of coupling with other semiconductors for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Synergistic effects and heterojunctions of ZnO-NiO within the nanofibers are crucial for enhancing photocatalytic efficiency. These heterojunctions facilitate charge transfer and reduce the recombination of electron-hole pairs, which are essential for effective photocatalysis [42]. The presence of NiO at a certain ratio (ZN1.5) correlates with increased photocatalytic activity due to an improved heterostructure, while maintaining the surface area [43].…”
Section: Photocatalytic Degradation Of Acetaminophen Using Zno-nio Hy...mentioning
confidence: 99%
“…Synergistic effects and heterojunctions of ZnO-NiO within the nanofibers are crucial for enhancing photocatalytic efficiency. These heterojunctions facilitate charge transfer and reduce the recombination of electron-hole pairs, which are essential for effective photocatalysis [42]. The presence of NiO at a certain ratio (ZN1.5) correlates with increased photocatalytic activity due to an improved heterostructure, while maintaining the surface area [43].…”
Section: Photocatalytic Degradation Of Acetaminophen Using Zno-nio Hy...mentioning
confidence: 99%
“…17 Numerous studies have explored the synthesis and application of n-type ZnO-based semiconductor materials in combination with other materials. For instance, Puttarajuet al 18 developed ZnO/NiO nanocomposites using Phyllanthusniruri L. extract for photocatalytic and biological activities. Bordbar et al 19 reported the green synthesis of CuO/ZnO nanocomposite using Melissa Officinalis L. leaf extract for photocatalytic degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have explored the synthesis and application of n-type ZnO-based semiconductor materials in combination with other materials. For instance, Puttarajuet al 18 developed ZnO/NiO nanocomposites using Phyllanthusniruri L . extract for photocatalytic and biological activities.…”
Section: Introductionmentioning
confidence: 99%